How Electronic Cigarette Affects the Vascular System. (30th September 2022) - Damay, Vito Anggarino; Setiawan, Setiawan; Lesmana, Ronny; Akbar, Mohammad Rizki; Lukito, Antonia Anna
Abstract : The popularity of the electronic cigarette has soared in the last decades. However, the health effect of smoking electronic cigarettes on the vascular system is unclear. This systematic review examines the electronic cigarettes' effect on the vascular system from recent evidence. A systematic search was conducted in MEDLINE (PubMed) database from January 2016 to August 2021 for studies assessing the vascular effect of chronic use of electronic cigarettes on human and animal. The Cochrane Risk of Bias 2, NIH Quality Assessment for Cross-Sectional Study, and SYRCLE's Risk of Bias were used to assess the risk of bias in interventional, observational, and animal study, respectively. A narrative synthesis of evidence is provided to describe results. From 101 retrieved studies related to electronic cigarettes effect on the vascular system, a total of 16 studies are included in this review. The overall results indicated that electronic cigarette use is associated with adverse events in the vascular, including the incident of elevated oxidative stress, endothelial dysfunction, inflammation, arterial stiffness, and the development of atherosclerotic lesion. Further studies should broaden perspectives and reveal more about the mechanism of how electronic cigarettes impact on vascular system.